2019
DOI: 10.1177/2277401720972852
|View full text |Cite
|
Sign up to set email alerts
|

Penological Justifications as Sentencing Factors in Death Penalty Sentencing

Abstract: When the Supreme Court of India upheld the constitutionality of the death penalty in Bachan Singh v. State of Punjab in 1980, it also laid down a sentencing framework for subsequent sentencing courts, guiding them in deciding between life imprisonment and the death penalty. This framework, popularly known as the ‘rarest of rare’ framework, was focused on individualised punishment. However, subsequent judgments have strayed away from Bachan Singh’s core framework, and the use of penological justifications as se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…For example, it is the poorest and most marginalised litigants who are unable to hire a lawyer to represent them or find the money for surety (bail) and face much higher chances of detention, incarceration, destitution and lack of social support. Studies on undertrials [16], those convicted and under sentence of death have demonstrated that most of them come from the poorest, the scheduled castes, scheduled tribes, nomadic tribes, and the Muslim community, since they face a heightened bias in society. Undertrials often spend more time in jail before trial than they would have even if convicted.…”
Section: Increased Incarceration Of the Most Underprivileged And Mino...mentioning
confidence: 99%
“…For example, it is the poorest and most marginalised litigants who are unable to hire a lawyer to represent them or find the money for surety (bail) and face much higher chances of detention, incarceration, destitution and lack of social support. Studies on undertrials [16], those convicted and under sentence of death have demonstrated that most of them come from the poorest, the scheduled castes, scheduled tribes, nomadic tribes, and the Muslim community, since they face a heightened bias in society. Undertrials often spend more time in jail before trial than they would have even if convicted.…”
Section: Increased Incarceration Of the Most Underprivileged And Mino...mentioning
confidence: 99%